Biogeographic Variation in Host Range Phenotypes and Taxonomic Composition of Marine Cyanophage Isolates - Hanson, China A.; Marston, Marcia F.; Martiny, Jennifer B. H. (Frontiers in Microbiology, 2016)
Despite the important role of phages in marine systems, little is understood about how their diversity is distributed in space. Biogeographic patterns of marine phages may be difficult to detect due to their vast genetic diversity, which may not be accurately represented by conserved marker genes. To investigate the spatial biogeographic structure of marine phages, we isolated over 400 cyanophages on Synechococcus host strain WH7803 at three coastal locations in the United States (Rhode Island, Washington, and southern California). Approximately 90% of the cyanophage isolates were myoviruses, while the other 10% were podoviruses. The diversity of isolates was further characterized in two ways: 1) taxonomically, using conserved marker genes and 2) phenotypically, by testing isolates for their ability to infect a suite of hosts, or their “host range”. Because host range is a highly variable trait even among closely related isolates, we hypothesized that host range phenotypes of cyanophage isolates would vary more strongly among locations than would taxonomic composition. Instead, we found evidence for strong biogeographic variation both in taxonomic composition and host range phenotypes, with little taxonomic overlap among the three coastal regions. For both taxonomic composition and host range phenotypes, cyanophage communities from California and Rhode Island were the most dissimilar, while Washington communities exhibited similarity to each of the other two locations. These results suggest that selection imposed by spatial variation in host dynamics influence the biogeographic distribution of cyanophages.